Uji Bakteri Coliform dan (Escherichia coli) pada Air Tercemar Dengan Penggunaan Susunan Filter - Linda Purwanti; Ahmad Syauqi; Saimul Laili (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2021)
Clean water is a serious problem in Indonesia, the availability of clean water has shrunk drastically due to deteriorating environment and pollution. Drinking water that meets safety standards is increasingly scarce. More than 100 million people need safe water sources. Filter media is able to remove chemicals in water such as turbid, odor, oily, yellowish, rusty and muddy making it unfit for consumption. In addition, the purpose of the clarification results must also be considered whether to drink household needs or other needs. This study uses Lauryl Tryptose Broth (LTB) media and petrifilm media. Petrifilm results show that it is very easy to count the bacteria Colifrom and Escerichia coli using petrifilm media. From the analysis of calculations using the Paired Samples T-Test on the sample before filtering and after filtering it was obtained the Tcount value of 2.28 with a P value 0.015 which showed very successful or significant results between the samples before and after the filter. In this analysis have normally distributed data with a significant value of P = 0.015 (<0.05). In this case the Paired Samples T-Test was tested for normality (Shapiro-Wilk) and the results were obtained in the form of a P value of <.001 which would indicate that the data was normally distributed, indicated by a P value <0.05. The filter on this filter is very useful for filtering on Escerichia coli bacteria because this filter removes the bacteria, but Colifrom bacteria can still escape the use of the filter, because it depends on environmental conditions. Colifrom and Escerichia coli bacteria occur is seen from the relationship between sources of pollution such as, for example, such as septic tanks, distance of wells with waste, trash, and livestock pollution. The quality of drinking water is very close to the presence of Colifrom and Escerichia coli bacteria which are likely to have pathogenic bacteria that are harmful to health in the quality of well water. Water samples to be observed using well water using 2 treatments as many as 12 repetitions. Thus the total sample obtained as many as 24 water samples will be observed. While the test making of Lauryl Triptose Broth medium was observed by incubating 48 hours at 35oC + gas. Before making the test tube medium must be sterilized first. Subsequent tests were observed with a petrifilm medium to determine the presence or absence of Colifrom and Escherichia coli bacteria by looking at the color of the battery being sought. Keywords: Drinking Water, Coliform Bacteria and Escherichia coli